Informatization and computerization of process of professional preparation of future teacher of physical culture is the future of athletic education in Ukraine. - Dragnev Y.V (Kharkov National Pedagogical University, 2011)
In the article informatization and computerization of process of professional preparation of future teacher of physical culture is examined. Specified on the improvement of all of on-line tutorials which it is necessary to do and offer to the future teachers of physical culture taking into account the world tendencies of informatization of education. It is marked that modern higher athletic education in informative society Ukraine must show by itself component part of this society, to answer the requirements of contemporary in relation to informatization of education in general, to give possibility the future teacher of physical culture to promote the level of computer literacy.